Respuesta :

Answer:

[tex]y = 2.096[/tex] or [tex]y = \frac{2\sqrt5+6}{5}}[/tex]

Step-by-step explanation:

Given

[tex]y = \frac{4}{x} + \sqrt x + 0.2 - 5x[/tex]

[tex]x = \frac{4}{5}[/tex]

Required

Find y

[tex]y = \frac{4}{x} + \sqrt x + 0.2 - 5x[/tex]

Substitute [tex]x = \frac{4}{5}[/tex]

[tex]y = \frac{4}{4/5} + \sqrt{4/5} + 0.2 - 5 * 4/5[/tex]

[tex]y = 5 + \sqrt{4/5} + 0.2 - 4[/tex]

Collect like terms

[tex]y = \sqrt{4/5} + 5 + 0.2 - 4[/tex]

[tex]y = \sqrt{\frac{4}{5}} + 1.2[/tex]

Split the surd

[tex]y = \frac{\sqrt4}{\sqrt5}} + 1.2[/tex]

[tex]y = \frac{2}{\sqrt5}} + 1.2[/tex]

Rationalize

[tex]y = \frac{2\sqrt5}{\sqrt5*\sqrt5}} + 1.2[/tex]

[tex]y = \frac{2\sqrt5}{5}} + 1.2[/tex]

Take LCM and add

[tex]y = \frac{2\sqrt5+1.2*5}{5}}[/tex]

[tex]y = \frac{2\sqrt5+6}{5}}[/tex]

or solve as:

[tex]y = \frac{2*2.24+6}{5}}[/tex]

[tex]y = \frac{10.48}{5}[/tex]

[tex]y = 2.096[/tex]